Mental illness and the legal rights of the individual / Helena Hashim - Hashim, Helena (Faculty of Law, 1988)
Much of the ancient-day myth concerning mental illness still remains a present day phenomena and it is not surprising to find that in Malaysia, the mentally abnormal/mentally illness patients are very commonly treated as outcast. This project paper is about the Law and its relationship to mentaI iIIness; and important subject. since any of us might suffer from a mental illness and as a result become involved with the Iaw in some way. Not only does one in ten of the population suffer from an actual mental 'illness at some time in life, many more are affected by emotional disturbances. It is the writer's hope that the writing of this paper will arouse greater public interest in the subject and in so doing to further remove the public prejudice heaped upon the unfortunate victims of mental illness. This is important as public cooperation is very necessary for the rapid rehabilitation of these patients. So it is useful for everyone to know something about psychiatry and the law in general, and about their interaction in particular.